The JEM-EUSO mission: An introduction - Adams, J. H. (2015)
The Extreme Universe Space Observatory on board the Japanese Experiment Module of the International Space Station, JEM-EUSO, is being designed tosearch from space ultra-high energy cosmic rays. These are charged particles with energies from a few 10^19 eV to beyond 10^20 eV, at the very end of the known cosmic ray energy spectrum. JEM-EUSO will also search for extreme energy neutrinos, photons, and exotic particles, providing a unique opportunity to explore largely unknown phenomena in our Universe. The mission, principally based on a wide field of view(60 degrees) near-UV telescope with a diameter of ~2.5 m, will monitor the earth?s atmosphere at night, pioneering the observation from space of the ultraviolet tracks (290-430 nm) associated with giant extensive air showers produced by ultra-high energy primaries propagating in the earth?s atmosphere. Observing from an orbital altitude of ~400 km, the mission is expected to reach an instantaneous geometrical aperture of A_geo >= 2 x 10^5 km^2 sr with an estimated duty cycle of ~20%. Sucha geometrical aperture allows unprecedented exposures, significantly larger than can be obtained with ground-based experiments. In this paper we briefly review the history of space-based search for ultra-high energy cosmic rays. We then introduce the special issue of Experimental Astronomy devoted to the various aspects of such a challenging enterprise. We also summarise the activities of the on-going JEM-EUSO program.